Estimation of Energy Dissipation of Flow Over Stepped Spillways - Farzin Salmasi; John Abraham (Engineering Research: Perspectives on Recent Advances Vol. 2, 2025)
Stepped spillways have been used since ancient times, about 3500 years ago. In a stepped spillway, the spillway face is provided with a series of steps from near the crest to the toe. This type of spillway is attractive for water resource management because it dissipates energy that is within the flow. When energy is dissipated by the steps, it reduces the energy reduction that otherwise must occur at the toe of the spillway. Air entrainment inflates the water flow over stepped spillways; the bulking of water due to high air entrainment forces designers to use a greater height for sidewalls in stepped spillways and for the downstream stilling basins. The purpose of this research is to investigate the energy dissipation rate in spillways with different slopes. In the present study, nine physical stepped spillway models with slopes of 15, 25, and 45 degrees and with a number of steps varying from 5 to 50 have been constructed. The crest of the spillways has standard Ogee profiles and a constant slope extends from the crest to the spillway toe. Two different-sized flumes were used in the experiments (25 and 50 cm wide). Several physical models have been constructed in order to measure the energy dissipation. The result revealed that the two most important dimensionless factors influencing energy dissipation are the Froude number and q2/(gHdam3). Here q is the discharge per unit width of the spillway (m3/s/m), Hdam is equal to the height of the spillway and g is the acceleration of the Earth’s gravity equal to 9.81 m/s2. The results showed that slope alone is not an effective factor for energy dissipation and should be used in combination with other factors. The spillway slope and step number have less impact on the rate of energy dissipation. But for a constant discharge over a stepped spillway, increasing the spillway slope, and increasing the number of steps will increase the energy dissipation. Using multiple regressions, some useful relations for determination energy dissipating are obtained.